Adhesive small-bowel obstruction treatment using internal intestinal splinting with a nasointestinal ileus tube - Cui, H; Jiang, X; Li, H (Minerva chirurgica, 2015)
The aim of this paper was to investigate the effect of non-surgical internal intestinal splinting using an ileus tube under X-ray guidance. Sixteen patients with recurrent postoperative adhesive small bowel obstruction (SBO) received internal splinting using intubation of a 300 cm long ileus tube. Under X-ray guidance, the tube was advanced through nose, 10 cm beyond the jejunal ligament of Treitz. The tube was advanced towards the end of ileum and propelled by peristalsis using a water-filled anterior balloon of the tube, which directly dilated narrowed intestines. The tube remained in the intestine for further support and splinting. All 16 patients achieved a resolution of the bowel obstruction without complications. During a follow-up of 8 months to 2 years, 1 patient had a recurrent obstruction 4 months post-procedure. The remaining patients did not experience obstruction recurrence. Non-surgical, internal intestinal splinting using a nasointestinal ileus tube under X-ray was simple, non-invasive, safe and effective treatment of recurrent adhesive SBO.